Health and healthcare variables associated with Italy's excess mortality during the first wave of the COVID-19 pandemic: An ecological study. Issue 4 (April 2022) - Buja, Alessandra; Paganini, Matteo; Fusinato, Riccardo; Cozzolino, Claudia; Cocchio, Silvia; Scioni, Manuela; Rebba, Vincenzo; Baldo, Vincenzo; Boccuzzo, Giovanna
Highlights: Healthcare factors have strongly influenced the propagation of COVID-19. A higher density of licensed physicians and General Practitioners is associated with lower excess mortality. Rate of hospitalization in long-term care wards and the cardiovascular disease mortality rate correlate with excess mortality. These variables should be modified to increase healthcare resilience. Abstract: Background: Healthcare factors have strongly influenced the propagation of COVID-19. This study aims to examine whether excess mortality during the first phase of the COVID-19 outbreak in Italy was associated with health, healthcare, demographic, and socioeconomic, provincial-level indicators. Methods: This ecological study concerns the raw number of deaths reported from February 1 to April 30, 2020 and the mean number of deaths occurred during the same months from 2015 to 2019, per province. Information on socioeconomic factors and healthcare settings was extracted from updated databases on the Italian National Institute of Statistics (ISTAT) website. A multivariate model and four multilevel models were constructed to test the association between excess mortality and the analysed indicators across 107 Italian provinces. Results: The hospitalization rate in long-term care wards and the cardiovascular disease mortality rate correlate positively with excess mortality (p <0.05), while higher densities of licensed physicians and of general practitioners are associated with lower excess mortality (p <0.05). After controlling for the COVID-19 cumulative incidence in each province, only the density of licensed physicians remains negatively associated with excess mortality (p <0.01). Conclusion: Some health and healthcare variables (in particular, the density of physicians) are strongly associated with excess mortality during the first wave of the COVID-19 pandemic in Italy and should be targeted to increase the resilience of health systems.